2021
DOI: 10.1007/jhep09(2021)120
|View full text |Cite
|
Sign up to set email alerts
|

Analytic results for two-loop planar master integrals for Bhabha scattering

Abstract: We analytically evaluate the master integrals for the second type of planar contributions to the massive two-loop Bhabha scattering in QED using differential equations with canonical bases. We obtain results in terms of multiple polylogarithms for all the master integrals but one, for which we derive a compact result in terms of elliptic multiple polylogarithms. As a byproduct, we also provide a compact analytic result in terms of elliptic multiple polylogarithms for an integral belonging to the first family o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…These analytic results were obtained in a recent paper [34] using differential equations with canonical bases. This is a two-loop example, but it already demonstrates well the advancement from FIESTA4 to FIESTA5.…”
Section: Physical Kinematics Comparing Versions and Options Of The Ne...mentioning
confidence: 56%
“…These analytic results were obtained in a recent paper [34] using differential equations with canonical bases. This is a two-loop example, but it already demonstrates well the advancement from FIESTA4 to FIESTA5.…”
Section: Physical Kinematics Comparing Versions and Options Of The Ne...mentioning
confidence: 56%
“…Conversely, it remains unclear whether other mechanism of generating functional relations between elliptic dilogarithms exist (although see [128,282] for work on this topic). Techniques for reducing elliptic multiple polylogarithms to multiple polylogarithms (when possible) also remain relatively unexplored, although there exist examples in which Feynman integrals containing multiple non-rationalizable square roots have been found to be expressible in terms of multiple polylogarithms [269,[284][285][286]. Importantly, methods for directly constructing the integrands of amplitudes using generalized unitarity [287][288][289] have also recently been extended to the elliptic sector.…”
Section: Iterated Integrals Involving Elliptic Curvesmentioning
confidence: 99%
“…Even in cases where the canonical " d log"-form of DEs can be obtained, it can be difficult, if not impossible, to find MPL solutions if the symbol alphabet contains non-rationalizable square roots [42,[54][55][56][57]. Very importantly, even when these attempts did succeed, it was frequently observed that the numerical evaluation in the physical scattering regions is very challenging [26,27,42,58]. In addition, contrary to naïve expectations, the physical properties may even be more obscured due to the presence of spurious branch cuts, which are instead absent in the iterated integral representation.…”
Section: Jhep01(2022)096 1 Introductionmentioning
confidence: 99%